Does Comprehensive Income Predict Future Cashflow Better Than Net Income? - Bayu Setyawan Suprayogi; Zuni Barokah (The Indonesian Journal of Accounting Research, 2019)
This study examines the ability of net income and comprehensive income in predicting future cash flows on publicly listed companies in Indonesia Stock Exchange. Further, this study also compares the ability of net income and comprehensive income in predicting future cash flows. Based on the sample of 1,735 firm-year observations of Indonesian listed companies for the financial years of 2011-2016, the result shows that both net income and comprehensive income have a significant relationship with future cash flows. However, we find that comprehensive income does not have a better capability than net income in predicting future cash flows.